Perceptions and Implementation Factors of the Bookworms Curriculum on Third through Fifth Grade Students’ Reading Performance - Miller, Autumn Hilary (My University, 2025)
This case study aimed to investigate the effectiveness of the Bookworms (BW) program in improving student reading performance among 128 students transitioning from third to fifth grade, who attended two public elementary schools in a rural school district. The school district utilized Lexile scores from GMAS during the 2020-2021, 2021-2022, and 2022-2023 academic years. This study also included the perceptions of teachers who taught the program, as assessed through a 30-item survey. Paired t-tests, independent t-tests, ANOVA, and chi-squared tests of independence were conducted to analyze the quantitative data. Qualitative data were coded to generate themes that help understand teachers’ perceptions of the Bookworms program. The results revealed the Bookworms program’s potential to support diverse learners regardless of gender and ethnicity. It seemed to benefit all learner service subgroups, particularly those in the Early Intervention Program (EIP). The teachers expressed reservations about the impact of Bookworms on student learning, but agreed that it helped enhance students’ vocabulary, comprehension skills, and overall reading performance. They emphasized the needs of (1) sufficient professional training, (2) specific guidelines on differentiated instruction, (3) specific guidelines for effectively using resources, (4) enough time for implementation, (5) appropriate resources to address the full spectrum of student reading needs, (6) scaling back the program and reduce the number of books, (7) incorporating additional instructions or supplemental materials resources such as phonics, grammar, worksheets, and assessments, and (8) allowing some flexibility from the scripted Bookworms curriculum to support effective program implementation.
Keywords: Dissertations, Academic--United States; Reading (Elementary); Reading comprehension; Education—Research; Education, Rural; School children; Lexile framework for reading; Public schools—United States; Educational surveys; Quantitative research; Qualitative research; Educational tests and measurements; Individualized instruction